Investigation on microstructure and mechanical properties of Al-Zn-Mg-Cu alloys with various Zn/Mg ratios. (20th September 2021) - Zou, Yan; Wu, Xiaodong; Tang, Songbai; Zhu, Qianqian; Song, Hui; Guo, Mingxing; Cao, Lingfei
Graphical abstract: Highlights: Influence of Zn/Mg ratios on the microstructure and mechanical properties was investigated systematically. The precipitation behavior of dual precipitates (T′ and η′ phase) has been discussed. T′ phase and η′ phase can co-exist, where a higher Zn/Mg ratio improves the precipitation of η′ phase. A strength model was established to predict the strengthening effect of dual precipitation (T′ and η′ phase). Abstract: The effects of Zn/Mg ratios on microstructure and mechanical properties of Al-Zn-Mg-Cu alloys aged at 150 °C have been investigated by using tensile tests, optical metallography, scanning electron microscopy, transmission electron microscopy and atom probe tomography analyses. With increasing Zn/Mg ratios, the ageing process is significantly accelerated and the time to peak ageing is reduced. T′ phase predominates in alloys of lower Zn/Mg ratios while η′ phase predominates in alloys with a Zn/Mg ratio over 2.86. Co-existence of T′ phase and η′ phase with a large number density is beneficial to the high strength of alloys. Such precipitates together with narrow precipitate free zones cause a brittle intergranular fracture. A strength model has been established to predict the co-strengthening effect of T′ phase and η′ phase in Al-Zn-Mg-Cu alloys, including the factors of the grain boundary, solid solution and precipitation.